Sperm-storage defects and live birth in Drosophila females lacking spermathecal secretory cells. - Schnakenberg, S.L.; Matias, W.R.; Siegal, M.L. (PLoS Biology, 2011)
Male Drosophila flies secrete seminal-fluid proteins that mediate proper sperm storage and fertilization, and that induce changes in female behavior. Females also produce reproductive-tract secretions, yet their contributions to postmating physiology are poorly understood. Large secretory cells line the female's spermathecae, a pair of sperm-storage organs. We identified the regulatory regions controlling transcription of two genes exclusively expressed in these spermathecal secretory cells (SSC): Spermathecal endopeptidase 1 (Send1), which is expressed in both unmated and mated females, and Spermathecal endopeptidase 2 (Send2), which is induced by mating. We used these regulatory sequences to perform precise genetic ablations of the SSC at distinct time points relative to mating. We show that the SSC are required for recruiting sperm to the spermathecae, but not for retaining sperm there. The SSC also act at a distance in the reproductive tract, in that their ablation: (1) reduces sperm motility in the female's other sperm-storage organ, the seminal receptacle; and (2) causes ovoviviparity--the retention and internal development of fertilized eggs. These results establish the reproductive functions of the SSC, shed light on the evolution of live birth, and open new avenues for studying and manipulating female fertility in insects.